Neo-glans reconstruction for penile cancer: Description of the primary technique using autologous testicular tunica vaginalis graft - Peter Weibl (Taylor & Francis Group, 2018)
Partial penectomy (glansectomy with/or without distal corporectomy) is an acceptable alternative for smaller distal pT3 penile carcinoma lesions in highly motivated and compliant patients. The authors describe a novel technique of neo-glans reconstruction using a tunica vaginalis (TV) testis allograft. However, due to an unclear resection margin on final histology, the patient underwent re-do surgery with a neo-glans revision using the well-established mesh split-thickness skin graft (STSG) technique. The penile length was preserved and the penile and bulbar part of the urethra was additionally mobilised in order to obtain a natural and aesthetic result for the meatus. Neo-glans reconstruction with TV coverage may be another promising alternative, which certainly requires further evaluation. We believe that the donor-site associated morbidity is minimal when compared to other harvesting sites. However, this is just an assumption, because direct comparison data on grafting techniques and neo-glans reconstruction are not available. Nevertheless, we think that for re-do procedures a standardised approach using a STSG technique should be the treatment method of choice.